THE IMPACT OF FINTECH ON THE DEVELOPMENT OF FINANCIAL INCLUSION IN MSME IN MATARAM - Ahadiah Agustina (IQTISHADUNA, 2022)
The purpose of writing this article is to find out how much influence fintech (risk andinvestment management, market provisioning, and cashless society) has on financial inclusion(financial knowledge, financial behavior, and financial attitudes) in MSMEs in Mataram city.The research conducted included quantitative research. The population of this study is theMSME industry in Mataram City by focusing on using archival data (archival method). Thisstudy uses descriptive analysis and classical assumption tests. The findings show thatsimultaneously and partially fintech variables (risk and investment management and marketprovisioning) have no effect on financial inclusion (financial knowledge, financial behavior, andfinancial attitudes) while simultaneously and partially, fintech variables (cashless society) affectfinancial inclusion (financial knowledge, financial behavior, and financial attitudes).